Effect of Gamification-Based Teaching on Junior Secondary School Student's Academic Performance in Mathematics in Kwara State - Attah, Justina Ojoma; Ogunlade, Oyeronke Olufumilola; Otemuyiwa, Bridget Idowu (Universitas KH. Abdul Chalim Pacet Mojokerto, 2024)
Gamification is a cutting-edge pedagogical approach to addressing student social behaviour, motivation, and academic performance in the classroom, particularly in subjects that are perceived to be difficult such as mathematics where there was a perceived failure. Hence, this study investigated the effect of gamification-based teaching on junior secondary school student’s academic performance in mathematics in Kwara State. The study adopted a quasi-experimental pretest-posttest, non-equivalent group design. The population was all junior secondary students in Kwara State while the target population were all junior secondary students in J.S.S. 2 in Kwara-North Senatorial district. A purposive sampling technique was used to select two junior secondary schools based on the availability of computer laboratories. A total of 122 students (experimental group 64; control group 58) were involved. Three instruments were used for data collection. Split-half was used to test the reliability of the instruments and coefficients of .89 were obtained Data collected were analyzed using descriptive and inferential statistics at 0.05 level of significance. The study revealed that; gamification-based teaching had a significant effect on the experimental group (F (1,54) = 1.826; p< 0.05) and female students in the experimental group significantly performed better than male students after the treatment. This study concluded that the use of gamification-based teaching in mathematics enhanced teaching-learning effectiveness in mathematics. The study, therefore, recommended among others, that mathematics teachers should use gamification in teaching mathematics to reduce the level of abstractness associated with teaching-learning of mathematics.